The Mechanism of Aluminum Vanadate in Aqueous Zinc Ion Batteries with Ultra-Long Cycle Life. Issue 3 (8th March 2021) - Su, Qingsong; Yang, Zhanhong; Chen, Linlin; Yuan, Liang; Chen, Hongzhe; Rong, Yao; Deng, Lie; Wu, Jian
Abstract : There are few cathode materials suitable for aqueous zinc ion batteries with high capacity and long cycle stability. Herein, H11 Al2 V6 O23.2 (defined as HAVO) microspheres are synthesized by hydrothermal method as cathode material, which exhibits a maximum discharge capacity of 236 mA g −1 at 100 mA g −1 . Significantly, ultra-long cycle performance of 100 mA g −1 with an extraordinary capacity retention of 90% is achieved after 5000 cycles at 8 A g −1 . The research finds that the excellent performance is attributed to the extraordinary layer spacing of 13.37 Å and reveals the zinc storage mechanism of the HAVO electrode.